REPRESENTASI KEHARMONISAN KELUARGA DALAM FILM KELUARGA CEMARA (ANALISIS WACANA VAN DIJK) - Dias Paramitha, Angella (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study aims to and reveal the values ​​of family harmony contained in the film Keluarga Cemara, especially in certain dialogues. This study uses library research using descriptive analysis methods, namely collecting data, or clarifying, compiling and interpreting it using the Van Dijk discourse analysis approach. Analyzing how the discourse strategy is used to describe a person or a particular event as in this study wants to reveal the meaning contained in the dialogue of the Cemara Family film. The barometer of family harmony theory that the researchers chose in this study. There are three aspects of family harmony that researchers mean, namely: affection, communication and cooperation.From the research it was concluded that the harmony of the Cemara Family film can be used as a guide or example of a film that represents family harmony in reality based on the Gunarsa theory that the researcher uses. In the film Keluarga Cemara it is represented that the economy is not a determinant of family harmony. Harmony is represented in the form of affection, togetherness, understanding, cooperation, acceptance and a fair distribution of tasks based on agreement. Based on the research findings, it is recommended that film can be used as an effective media representation.